Wavelet cross-correlation and phase analysis of a free cantilever subjected to band excitation - Francesco Banfi; Gabriele Ferrini (Beilstein Journal of Nanotechnology, 2012)
This work introduces the concept of time–frequency map of the phase difference between the cantilever response signal and the driving signal, calculated with a wavelet cross-correlation technique. The wavelet cross-correlation quantifies the common power and the relative phase between the response of the cantilever and the exciting driver, yielding “instantaneous” information on the driver-response phase delay as a function of frequency. These concepts are introduced through the calculation of the response of a free cantilever subjected to continuous and impulsive excitation over a frequency band.